Suboptimal Inspiratory Flow Rates With Passive Dry Powder Inhalers: Big Issue or Overstated Problem? - Weers, Jeffry (Frontiers in Drug Delivery, 2022)
The premise that subjects must overcome the internal resistance of a DPI to achieve a peak inspiratory flow rate of 60 L min-1 12 for effective powder fluidization and deagglomeration of inhaled bronchodilators for the treatment of COPD is fundamentally incorrect. This reliance on a 60 L min-1 13 14 minimum flow leads to a significant overestimate of the percentage of patients with suboptimal flow 15 rates, and this criterion should not be used as a biomarker to guide transition of patients to an active 16 device. Alternatively, the minimum threshold energy for effective drug delivery with passive dry 17 powder inhalers (DPI) occurs at peak inspiratory pressures greater than or equal to about 1 kPa, 18 independent of the internal resistance of the device. Most patients can achieve the threshold 1 kPa 19 pressure drop even during periods of acute wheeze.